Trinucleotide Repeat Expansion in the TCF4 Gene in Fuchs' Endothelial Corneal Dystrophy in Japanese - Nakano, Masakazu; Okumura, Naoki; Nakagawa, Hiroko; Koizumi, Noriko; Ikeda, Yoko; Ueno, Morio; Yoshii, Kengo; Adachi, Hiroko; Aleff, Ross A.; Butz, Malinda L.; Highsmith, W. Edward; Tashiro, Kei; et al. (Investigative ophthalmology & visual science, 2015)
The purpose of this study was to evaluate the association between the intronic expansion of a trinucleotide repeat (TNR) in the TCF4 gene and Fuchs' endothelial corneal dystrophy (FECD) in a Japanese population. Forty-seven Japanese FECD patients and 96 age-matched controls were recruited. FECD patients and controls were examined by slit-lamp and noncontact specular microscopy. The repeat length was determined by direct sequencing and short tandem repeat assay of PCR-amplified DNA and Southern blotting of unamplified DNA. A TNR expansion, defined as >50 CTG repeats in the TCF4 gene was identified in 12 of 47 FECD cases (26%) and 0 of 96 controls (0%; P < 0.001). Sensitivity and specificity in this study were 26% and 100%, respectively. The clinical characteristics of FECD patients with TNR expansion were not distinct from those without TNR expansion. These findings show for the first time in a Japanese population the association of the TNR expansion in TCF4 with FECD. In contrast to Caucasian cohorts in whom the TNR expansion is present in most patients with FECD, a CTG expansion is present in a minority of Japanese subjects, indicating other genetic variants as common causes of phenotypically identical disease in this population.